X-ray absorption spectroscopy as a tool investigating arsenic(III) and arsenic(V) sorption by an aluminum-based drinking-water treatment residual - Makris, Konstantinos C.; Sarkar, Dibyendu; Parsons, Jason G.; Datta, Rupali K.; Gardea-Torresdey, Jorge Luis (My University, 2009)
Historic applications of arsenical pesticides to agricultural land have resulted in accumulation of residual arsenic (As) in such soils. In situ immobilization represents a cost-effective and least ecological disrupting treatment technology for soil As. Earlier work in our laboratory showed that drinking-water treatment residuals (WTRs), a low-cost, waste by-product of the drinking-water treatment process exhibit a high affinity for As. Wet chemical experiments (sorption kinetics and desorption) were coupled with X-ray absorption spectroscopy measurements to elucidate the bonding strength and type of As(V) and As(III) sorption by an aluminum-based WTR. A fast (1 h), followed by a slower sorption stage resulted in As(V) and As(III) sorption capacities of 96% and 77%, respectively. Arsenic desorption with a 5 mM oxalate from the WTR was minimal, being always <4%. X-ray absorption spectroscopy data showed inner-sphere complexation between As and surface hydroxyls. Reaction time (up to 48 h) had no effect on the initial As oxidation state for sorbed As(V) and As(III). A combination of inner-sphere bonding types occurred between As and Al on the WTR surface because mixed surface geometries and interatomic distances were observed.
Keywords: Residuals; Drinking-water; Arsenic (As); XANES; EXAFS